The Effect of the Use of Augmented Reality (Ar) on Purchase Decision of L'oreal Cosmetic Products at Tokopedia Beauty - Imron Maulana; Ajen Campakararang; Firstyo Dewo Wicaksono (Eduvest - Journal of Universal Studies, 2024)
This study investigates the influence of Augmented Reality (AR) technology on consumer purchase decisions regarding L'Oréal cosmetic products within the context of Tokopedia Beauty, an e-commerce platform. With the increasing integration of AR in online shopping experiences, understanding its effect on consumer behavior is imperative for businesses and marketers. Through a quantitative approach, this research analyzes consumer perceptions and attitudes towards AR-enabled product visualization and its impact on purchase decisions. Data is collected through surveys distributed among Tokopedia Beauty users, assessing their experiences with AR features and subsequent purchasing behavior. The findings elucidate the significant role of AR in enhancing consumer engagement and confidence in product selection, ultimately influencing purchase decisions positively. The implications of these findings offer valuable insights for both practitioners and researchers in leveraging AR technology to optimize online cosmetic shopping experiences and drive sales.